English Premier League (EPL) Soccer Matches Prediction using An Adaptive Neuro-Fuzzy Inference System (ANFIS) - Amadin, Frank; Chukwuyeni Obi, Jonathan (Transactions on Engineering and Computing Sciences, 2015)
Prediction of English Premiership League (EPL) matches has been on the heart and minds of researcher over the pass decades, but none has sufficiently introduced and Adpative Neuro-Fuzzy Inference System (ANFIS) approach for these prediction which has served as the focal aim of this research paper using seven premier league teams and nine linguistic values. Matric Laboratory (MATLAB) 7.0 served as the tool of implementation highlighting various views. The ANFIS training was successful completed at epoch 2 and having an error of 1.41237e-006. The model was further used to predict the outcome of 7 matches with a successful rate of 71%.